Distance Interaction in Corporate Management - T. I. Zakharova (Plekhanov Russian University of Economics, 2020)
The article studies innovation methods of distance interaction in the system of international corporate management. The necessity to initiate distance communications is stipulated not only by the need to extend business territory, to open regional branches, to attract employees from different countries and cities but also by the current situation with the global pandemia. On 11 March 2020 the WHO called the outbreak of the new type of corona-virus COVID-19 a pandemia, which changed drastically traditional way of life, business, education all over the world. For millions of people distance communications became the only tie with the world. The need in remote work affected the current trends in the field of corporate management, in particular the system of HR management in organizations. As a result of the research the author formulated a number of recommendations aimed at optimization of interaction at all levels of management, as passing-over to the distance format requires the availability of effective tools for automation of HR service functions (employment and selection of personnel, its appraisal and training) and efficient and rational planning, business communications, distribution of functions and tasks by using information technologies.